Innovation and precarity: Workplace discourse in twenty-first century capitalism - Sidney A. Rothstein (Max Planck Institute for the Study of Societies, 2019)
This paper analyzes discourse in the workplace in order to explain puzzling patterns of precarity in twenty-first century capitalism. Tech workers' central role in digital transformation endows them with labor market power reflected by their high wages, but during economic downturns, when demand for their skills decreases, even they are vulnerable to downsizing. Comparing workers' responses to downsizing at two sites of an American tech firm, this paper shows how management disempowers workers by framing the employment relationship in a financial discourse. Disposing workers to believe that their jobs are threatened by market forces beyond their control, rather than by managers' decisions, this financial discourse undermines labor's established power resources by persuading workers that mobilizing will be ineffective in protecting their jobs. Relying on detailed case study evidence, this paper demonstrates the importance of discourse to explaining variation in worker power. It argues that the workplace should play a larger role in comparative political economy, particularly in explaining labor market outcomes related to digital transformation. – – Dieses Papier trägt zum Verständnis von Prekarität im Kapitalismus des 21. Jahrhunderts bei, indem es den Blick auf betriebliche Diskurse lenkt. Durch ihre zentrale Rolle bei der digitalen Transformation haben Arbeitnehmer der Technologiebranche auf dem Arbeitsmarkt eine starke Position, ausgewiesen durch ihre hohen Löhne. Aber auch sie sind bei Restrukturierungen verwundbar, wenn im Abschwung die Nachfrage nach ihren Fertigkeiten zurückgeht. Das Papier vergleicht die Reaktionen der Beschäftigten auf Restrukturierungen in zwei Niederlassungen eines amerikanischen Technologieunternehmens und zeigt, wie ihre Position geschwächt wird, wenn die Unternehmensleitung das Beschäftigungsverhältnis im Rahmen eines Finanzdiskurses darstellt. Sie schürt den Glauben, dass Mobilisierung auf Arbeitnehmerseite nicht weiterhilft, weil nicht etwa Entscheidungen der Unternehmensleitung, sondern unkontrollierbare Marktkräfte die Arbeitsplätze bedrohen, und unterminiert die Machtressourcen der Beschäftigten. Im Ergebnis verdeutlicht das Papier den Stellenwert diskursiver betrieblicher Faktoren zur Erklärung unterschiedlicher Reichweiten von Arbeitnehmermacht. Geht es um den Arbeitsmarkt im Kontext der digitalen Transformation, sollten am Arbeitsplatz ansetzende Analysen in der Vergleichenden Politischen Ökonomie stärker zum Einsatz kommen.
hdl:21.11116/0000-0004-B3F1-1
Keywords: 300; capitalism; discourse; hegemony; knowledge economy; power; workers; Arbeitnehmer; betriebliche Diskurse; Hegemonie; Kapitalismus; Macht; Wissensökonomie